The intention to leave among nurses: the role of job satisfaction, self-efficacy and work engagement - De Simone, Silvia; Planta, Anna (La Medicina del Lavoro, 2017)
Introduction: Retaining nursing staff within hospitals is essential to limit the negative impact of excessive voluntary turnover on the quality of care and organization costs. Objectives: The purpose of this study is to explain voluntary turnover in the nursing profession by analyzing the influence of job satisfaction and, in particular, self-efficacy and work engagement on turnover intention. Methods: 210 nurses working in three hospitals in Southern Italy have completed a self-report questionnaire. A correlation analysis was applied in order to test the relationship between variables, while the role of age, professional and organizational seniority was estimated through partial correlations. A multiple linear regression was performed to verify the role of self-efficacy and work engagement in predicting turnover intention. Results: Job satisfaction, self-efficacy and work engagement are positively correlated. These dimensions are negatively correlated with the intention to change the hospital; furthermore, age, professional and organizational seniority have an effect on this relationship. Work engagement fully mediates the relationship between self-efficacy and turnover intention. Conclusions: Results highlight the importance of considering not only job satisfaction, but also self-efficacy and work engagement, in studies on turnover intentions. These findings suggest to implement actions to increase self-efficacy, and especially work engagement, to reduce the voluntary turnover of nursing staff.